HEAT RESISTANCE OF FURNITURE PARTS COVERED BY PLASMA TREATED FOILS - Ján, Sedliačik; Tomasz, Krystofiak; Pavol, Antal; Mária, Šmidriaková; Lis, Barbara (Innovation in Woodworking Industry and Engineering design, 2013)
Surface finish of furniture parts with foils is very popular way of decorative 3D–finish of furniture. As the foil is a thermoplastic material, for furniture parts used in interiors of bathroom or kitchen it is important to be water resistant and heat resistant. We tested polyethylene (PET) and polyvinylchloride (PVC) foils with 9 various colourations and gloss, 4 types of polyurethane based dispersions and two press settings. MDF was used as the base board. Surface of selected foil types was modified by electric discharge plasma. Measurement of the contact angle Θ of the surface of foils was done with distilled water as wetting liquid, according to EN 828. Estimation of the adherence of foils to the substrate with the pull-off method was done according to the procedure EN ISO 4624. Heat resistance of glued joint was tested by heating the samples in a chamber at temperatures from 50 °C to heat destruction. The appearance and damage of all tested samples were assessed visually. The results have shown that the type of adhesive, type of foil and vacuum pressing process are significant for joint quality. Heat resistance can be increased up to 20 or 30 °C by proper setting of the pressing process. Appearance was improved on plasma treated samples.